PENINGKATAN KESEJAHTERAAN RAKYAT MENGGUNAKAN KONSEP DESENTRALISASI MELALUI OTONOMI DAERAH DI KEPULAUAN BANGKA BELITUNG - Suci Diana Sari; Jorgian Farsi; Basir Basir; Noveni Delianti (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Decentralization is one form of embodiment in the transfer of central government power to the region using the principle of autonomy. This decentralization has referred to Law No. 23 of 2014 where local governments can organize government on the basis of autonomy and assistance duties using the principle of free autonomy in the system of the Unitary State of the Republic of Indonesia. Of course, in the face of all the problems that are being experienced by the local government, there is no need to wait for instructions from the central government because of course it will take time and the process of solving problems is not handled quickly. Of course, with this decentralization, the government is more effective in accordance with the conditions in each region and also the community can advance its own area.